Molecular dynamics of laser-assisted decomposition of unstable molecules at the surface of carbon nanotubes: case study of CH2(NO2)2 on CNT(4, 0). (4th March 2017) - Disrud, Brendon; Han, Yulun; Kilin, Dmitri S.
ABSTRACT: In this study, photoreactions of the dinitromethane molecule noncovalently adsorbed on the (4, 0) carbon nanotube (CNT) have been investigated by time-dependent, excited-state molecular dynamics, which takes into account simultaneous evolution of electronic excitation and nuclear positions under periodic optical excitations. It is found that desorption of molecular adsorbate from CNT surface can be controlled by UV−vis photoexcitations. In addition, it is shown that the presence of CNT substrate facilitates photodecomposition of the adsorbate molecule, related to optically controlled explosion. This model demonstrates potential of photoinduced charge transfer between the adsorbate and substrate, which can affect efficiency of desorption and decomposition reactions. This process has a potential use as a remote trigger for larger scale detonations, or as a mechanism for 'cleaning' CNTs of unwanted functionalisation. GRAPHICAL ABSTRACT: